Bicycle Frame Design And Structural Analysis - İnce, Kutluay; Gül, Okan (International Conference on Applied Engineering and Natural Sciences, 2023)
With the development of technology, human beings, who can easily cover long distances, have not been able to give up bicycles, although they are advancing in the field of transportation every day. The bike is still attractive as it does not require long and costly maintenance, is light and handy. The human-powered bicycle is a nature and environment friendly vehicle in addition to motorized transportation vehicles. In this study, in general a bicycle frame design suitable for daily and mountain roads, ergonomically designed according to human body size was designed and the stresses and elongations that occur in the analysis programs were examined.